K : a biography of Kafka - Hayman, Ronald, 1932-2019 (London : Phoenix Press, 2001)
Een lijvige biografie van Franz Kafka, de auteur die we kennen van "Het proces", "Het slot", "De gedaanteverwisseling", ...
Includes bibliographical references (p. 335-339) and index.
Keywords: Kafka, Franz, -- 1883-1924.; Authors, Austrian -- 20th century -- Biography